2017
DOI: 10.1111/gcb.13952
|View full text |Cite
|
Sign up to set email alerts
|

Differential declines in Alaskan boreal forest vitality related to climate and competition

Abstract: Rapid warming and changes in water availability at high latitudes alter resource abundance, tree competition, and disturbance regimes. While these changes are expected to disrupt the functioning of boreal forests, their ultimate implications for forest composition are uncertain. In particular, recent site-level studies of the Alaskan boreal forest have reported both increases and decreases in productivity over the past few decades. Here, we test the idea that variations in Alaskan forest growth and mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…Our results (Figure a) confirm the idea that continued warming will increase aboveground biomass throughout portions of Alaska (Ackerman, Griffin, Hobbie, & Finlay, ), which may partly help curb carbon emissions from thawing permafrost (Abbott et al., ). In contrast, our results (Figure c) also suggest that plant productivity may decline in warming regions due to drought stress which would predispose woody vegetation to the risk of disease, fire, and mortality (Rogers et al., ; Trugman, Medvigy, Anderegg, & Pacala, ). Further research is needed to better understand climates impact on short and long term shifts in vegetation phenology, as well as to identify and quantify higher order interactions among environmental factors (e.g., climate, soil moisture) that influence vegetation productivity at a multitude of scales.…”
Section: Discussionmentioning
confidence: 99%
“…Our results (Figure a) confirm the idea that continued warming will increase aboveground biomass throughout portions of Alaska (Ackerman, Griffin, Hobbie, & Finlay, ), which may partly help curb carbon emissions from thawing permafrost (Abbott et al., ). In contrast, our results (Figure c) also suggest that plant productivity may decline in warming regions due to drought stress which would predispose woody vegetation to the risk of disease, fire, and mortality (Rogers et al., ; Trugman, Medvigy, Anderegg, & Pacala, ). Further research is needed to better understand climates impact on short and long term shifts in vegetation phenology, as well as to identify and quantify higher order interactions among environmental factors (e.g., climate, soil moisture) that influence vegetation productivity at a multitude of scales.…”
Section: Discussionmentioning
confidence: 99%
“…Conifer BA was our primary metric of competition. Although BA is a measure of stand productivity, it has also been successfully used as a measure of plot crowding as it integrates both stand density and tree size (Martin & Ek, ; Trugman et al, ). We focused on within conifer competition for two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Plot-specific details can be found in Appendix S1. leading defoliator in interior Alaska compared with other pests (Dubois and Burr 2015), (2) has reduced aspen photosynthesis and growth in experimental studies (Wagner et al 2008) and (3) has recently been observed as a leading cause of mortality among inventory plots in the Tanana Valley (Trugman et al 2017). We examined the relationship between growth and ALM population (insects/m 2 of foliage) using ring width indices for cores collected from Bonanza Creek LTER in 2015 (n = 18).…”
Section: Tree Growth Responses To Biotic Agentsmentioning
confidence: 99%
“…Although climate appears to have more limited direct effects on aspen radial growth than the other species investigated, a warmer and drier climate in recent decades may have had a stronger indirect effect on aspen growth by increasing this species vulnerability to herbivory and by initiating or exacerbating the severity of the ALM outbreak. The interaction between defoliators and moisture limitation in aspen stands could have major implications for forest productivity (Hogg et al 2008), mortality (Hogg et al 2002, Trugman et al 2017 and feedbacks to climate (Michaelian et al 2011) in the form of altered biogeochemical cycles and surface energy budgets.…”
Section: Climatic and Biotic Drivers Of Aspen Growthmentioning
confidence: 99%